Evidence Linking Cadmium Exposure and β2-Microglobulin to Increased Risk of Hypertension in Diabetes Type 2 - Supabhorn Yimthiang; Phisit Pouyfung; Tanaporn Khamphaya; David A. Vesey; Glenda C. Gobe; Soisungwan Satarug (Toxics, 2023)
The most common causes of chronic kidney disease, diabetes, and hypertension are significant public health issues worldwide. Exposure to the heavy metal pollutant, cadmium (Cd), which is particularly damaging to the kidney, has been associated with both risk factors. Increased levels of urinary β2-microglobulin (β2M) have been used to signify Cd-induced kidney damage and circulating levels have been linked to blood pressure control. In this study we investigated the pressor effects of Cd and β2M in 88 diabetics and 88 non-diabetic controls, matched by age, gender and locality. The overall mean serum β2M was 5.98 mg/L, while mean blood Cd and Cd excretion normalized to creatinine clearance (Ccr) as ECd/Ccr were 0.59 µg/L and 0.0084 µg/L of filtrate (0.95 µg/g creatinine), respectively. The prevalence odds ratio for hypertension rose by 79% per every ten-fold increase in blood Cd concentration. In all subjects, systolic blood pressure (SBP) showed positive associations with age (β = 0.247), serum β2M (β = 0.230), and ECd/Ccr (β = 0.167). In subgroup analysis, SBP showed a strong positive association with ECd/Ccr (β = 0.303) only in the diabetic group. The covariate-adjusted mean SBP in the diabetics of the highest ECd/Ccr tertile was 13.8 mmHg higher, compared to the lowest tertile (p = 0.027). An increase in SBP associated with Cd exposure was insignificant in non-diabetics. Thus, for the first time, we have demonstrated an independent effect of Cd and β2M on blood pressure, thereby implicating both Cd exposure and β2M in the development of hypertension, especially in diabetics.